“The word ‘Machu Picchu’ makes me very uncomfortable”: Racialized latinidades in Spanish higher education institutions - Vaillant-Cruz, G.; Olmos Alcaraz, A.; Padilla, B. (Migraciones, 2025)
The paper examines the racialization processes experienced by a group of university students identified as Latin American, Latino, and/or Afro-Latin American in Spain. Through ethnographic work conducted in higher education spaces, the research identifies three coping strategies for dealing with racialization experiences. The first occurs when participants are aware of these processes and the resulting racism, recognizing that it goes beyond phenotype (especially in bureaucratic processes and in relation with gender). The second strategy involves minimizing these racialization processes by labeling them as misunderstandings. The third strategy entails adopting resistance strategies to confront these processes, either by forming ethnoracial and/or religious communities or by actively engaging in anti-racist groups. In the conclusion, the article reflects on the persistence of colonial imaginaries about Latinidad present in the racialization processes experienced, interrelating them with the coping strategies present in the testimonies and connecting them with our concept of situational global racial formation.